Paths to infinity: Ancestorship, origin narratives and differentiation - Viegas, Susana de Matos (2021)
In November 2016, Rui Graça Feijó and I organized a round table in the Archive and Museum of the Timorese Resistance in Dili, centred around a photo exhibition we both curated. It comprehended a number of images of funerary posts named in Fataluku arapou cau1 (Fat: buffalo head), consisting of several metres high wooden posts with skulls of buffalos sacrificed at mortuary ceremonies. In the ensuing debate, two of our Fataluku interlocutors insisted that putting such funerary posts next to a tomb was not universal amongst Fataluku-speaking peoples. Amongst the variety of reasons aired by them and the audience, the social status of the deceased, the material wealth of his family, and the fact that some Fataluku were baptized (a condition that could militate against this possibility) have generated wide acceptance.